2019
DOI: 10.1186/s13756-019-0645-9
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the gut and environmental resistome in a community in northern Vietnam in relation to antibiotic use

Abstract: BackgroundAntibiotic resistance is a major global public health threat. Antibiotic use can directly impact the antibiotic resistant genes (ARGs) profile of the human intestinal microbiome and consequently the environment through shedding.MethodsWe determined the resistome of human feces, animal stools, human food and environmental (rain, well, and irrigative water) samples (n = 304) in 40 households within a community cohort and related the data to antibiotic consumption. Metagenomic DNA was isolated and qPCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 36 publications
4
28
1
Order By: Relevance
“…In other European countries, the prevalence of mcr - 1 in the community or among patients in hospitals was also low (0–0.4%) [ 22 , 23 , 24 ]. The travel-associated acquisition of mcr - E. coli is in agreement with findings of mcr - 1 carriage rates of 5–88% in China, Bolivia, and Vietnam [ 25 , 26 ]. In these countries, reports indicate a livestock- or food-associated exchange of mcr - E. coli .…”
Section: Discussionsupporting
confidence: 85%
“…In other European countries, the prevalence of mcr - 1 in the community or among patients in hospitals was also low (0–0.4%) [ 22 , 23 , 24 ]. The travel-associated acquisition of mcr - E. coli is in agreement with findings of mcr - 1 carriage rates of 5–88% in China, Bolivia, and Vietnam [ 25 , 26 ]. In these countries, reports indicate a livestock- or food-associated exchange of mcr - E. coli .…”
Section: Discussionsupporting
confidence: 85%
“…AMR determinants can move between bacterial populations through horizontal gene transfer. As a result, microbiota and resistome traits are not always strongly aligned, and indeed, intestinal microbiota depletion can result in increased acquisition of resistant bacteria from the environment [30]. However, in our study population, microbiota diversity was not significantly correlated with the number of AMR genes carried and was unrelated to patient location.…”
Section: Discussioncontrasting
confidence: 56%
“…Recent studies suggest that through feces, humans and domestic animals disseminate antibiotic resistant bacteria into the environment (41). Our previous report showed that antibiotic resistance genes were detected in water at low proportion as compared to humans and animals (42). Along with the antibiotic pollution in water resources, antibiotic resistant microbes might become a part of water microbiota (43).…”
Section: Discussionmentioning
confidence: 99%
“…The demographics of this complete cohort have been described in our previous study, which was designed to explore the circulation of ARGs in humans, animals and their environment (42) (see supplementary-Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation